2020
DOI: 10.1093/ofid/ofaa251
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Compositional and Functional Disruption of the Gut Microbiota in Typhoid Fever and Nontyphoidal Febrile Illness

Abstract: Background Experimental murine models and human challenge studies of Salmonella Typhi infection have suggested that the gut microbiome plays an important protective role against the development of typhoid fever. Anaerobic bacterial communities have been hypothesized to mediate colonization resistance against Salmonella species by producing short-chain fatty acids, yet the composition and function of the intestinal microbiota in human patients with typhoid fever remain ill defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Second, we were not able to determine the levels of short-chain fatty acids in this cohort, as the medium that was used in the rectal swab collection tubes impeded us to do metabolomic analyses. Nevertheless, we have validated the relationship between the abundance of these butyrate-producing bacteria and the absolute concentrations of all SCFAs in recent publications [24,47] and are therefore confident that an absence of these bacteria leads to intestinal depletion of these metabolites.…”
Section: Discussionsupporting
confidence: 65%
“…Second, we were not able to determine the levels of short-chain fatty acids in this cohort, as the medium that was used in the rectal swab collection tubes impeded us to do metabolomic analyses. Nevertheless, we have validated the relationship between the abundance of these butyrate-producing bacteria and the absolute concentrations of all SCFAs in recent publications [24,47] and are therefore confident that an absence of these bacteria leads to intestinal depletion of these metabolites.…”
Section: Discussionsupporting
confidence: 65%
“…This finding proves that there is a direct link between the presence of S. Typhi and the abundance of Lactobacillus species. This is in tandem with a recent study by Haak et al (2020), who reported that patients with typhoid fever had significantly altered patterns of compositional and functional disruption of the gut microbiota compared with healthy persons. In the same study, typhoid fever subjects were found to be significantly more colonised by other pathogens, with a significant decrease in the population of beneficial bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the composition of the gut microbiota in pigs' cecum was found to change as a result of infections with S. Typhimurium, according to a recent study (Borewicz et al, 2015). Alteration of the intestinal microbiota by S. Typhi has been attributed to the aerobic expansion of the intestinal environment, leading to the loss of obligate anaerobes (Haak et al, 2020). Loss or reduction of obligate anaerobes (commensals) has been shown to increase the risk of gastrointestinal infection due to reduced colonisation resistance (Haak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that gut microbiota plays a certain role in the pathogenesis of febrile diseases, such as familial Mediterranean fever 23 and typhoid fever. 24 However, whether gut microbiota affects the presence of fever in COVID-19 patients is currently unknown. Through MWAS, we found that the abundance of E. faecalis, C. freundii, C. unclassified, H. parainfluenzae , and S. cerevisiae in the guts of COVID-19 patients with fever were significantly higher than in COVID-19 patients with non-fever.…”
Section: Discussionmentioning
confidence: 99%